RE/UN/DIScover Heuristic: Working with Clinical Practice Impingements in Dehumanizing Times - Keenan, Elizabeth King (Clinical Social Work Journal, 2023)
Although clinical social work seeks to center the transformative potential of human relationships, practitioners are experiencing heightened systemic and organizational impingements from the dehumanizing pressures of neoliberalism. Neoliberalism and racism diminish the vitality and transformative potential of human relationships, disproportionately affecting Black, Indigenous and People of Color (BIPOC) communities. Practitioners are also experiencing increased stress and burnout related to increased caseloads and decreased professional autonomy and organizational practitioner support. Holistic, culturally responsive, and anti-oppressive processes seek to counter these oppressive forces but need further development to synthesize antioppressive structural understandings with embodied relational interactions. Practitioners can potentially contribute to efforts that apply critical theories and antioppressive understandings within their practice and workplace. Through an iterative flow of three sets of practices, the RE/UN/DIScover heuristic supports practitioners’ efforts to respond in those challenging everyday moments where oppressive forms of power are imposed and embedded within systemic processes. With themselves and other colleagues, practitioners engage in compassionate REcover practices; use curious, critical reflection to UNcover full understandings of power dynamics, impacts, and meanings; and draw on creative courage to DIScover and enact socially just and humanizing responses. This paper describes how practitioners can use the RE/UN/DIScover heuristic in two common challenging moments of clinical practice: systemic practice impingements and implementing a new training or practice model. The heuristic seeks to support practitioners’ efforts to preserve and expand socially just, relational spaces for themselves and those with whom they work within the context of systemic dehumanizing neoliberal forces.
Keywords: Clinical practice; Heuristic; Neoliberalism; Power; Practice challenges; Window of tolerance; dept.swk; peer-reviewed